Poly(ethylene glycol)-graft-poly(vinyl acetate) single-chain nanoparticles for the encapsulation of small molecules. Issue 6 (26th January 2017) - Bartolini, Arianna; Tempesti, Paolo; Resta, Claudio; Berti, Debora; Smets, Johan; Aouad, Yousef G.; Baglioni, Piero
Abstract : Amphiphilic poly(ethylene glycol)- graft -poly(vinyl acetate) copolymers with a low degree of grafting undergo self-folding in water driven by hydrophobic interactions, resulting in single-chain nanoparticles (SCNPs) possessing a hydrodynamic radius of about 10 nm. Abstract : Amphiphilic poly(ethylene glycol)- graft -poly(vinyl acetate) copolymers with a low degree of grafting undergo self-folding in water driven by hydrophobic interactions, resulting in single-chain nanoparticles (SCNPs) possessing a hydrodynamic radius of about 10 nm. A temperature scan revealed a lower critical solution temperature (LCST)-type phase behavior. In addition, SAXS data collected close to the LCST showed that these SCNPs aggregate into one-dimensional elongated objects, preferentially. With respect to the typical linear complex-structured polymer chains, this material is ideally suited for industrial and/or biomedical applications because of its simple molecular architecture and persistence of SCNPs up to 100 mg mL −1 . The so-obtained single-chain globular particles are able to swell upon loading with small hydrophobic molecules therefore promoting solubilization of flavors or drugs, which could be of interest in the food and pharmaceutical industry.